Occupational risk assessment: review of wooden scaffold board application in Malaysian oil and gas industry - Mohd Jamil Abdul Wahab; Noor Azrieda Abd Rashid; Salmiah Ujang; Lim, Seng Choon (Penerbit Universiti Kebangsaan Malaysia, 2016)
Timber scaffold boards have been widely utilised in the offshore construction industry. However, technical specifications and inspection procedure for the application of scaffold boards from a wood material were inadequate. In the development of the standard requirements, evaluation of actual engineering practices could indicate the level of workplace safety. A study was conducted to identify risk and safety measures concerning the use of timber scaffold boards in construction. This article discusses on the occupational risks and ergonomics issues of the scaffolding application based on the physical and mechanical conditions of tropical timber scaffold boards extracted from offshore oil and gas rigs. The boards were exposed to a seasonal climate of East Coast monsoon of South China Sea between November and February. The scaffolding application extended up to 20 m directly above the ocean surface and some boards were completely immersed below the ocean surface particularly during elevated tidal waves. Some of the boards were installed as the on-deck platforms. Forty scaffold boards fabricated from tropical timber species were evaluated. Physical characteristics of the boards were described by natural and man-made factors. A three-point bending test was conducted to determine the maximum load capacity of each board and the mode of fracture was evaluated. Timber identification test was conducted to identify the groups of the timber being used. The microscopic observation confirmed the presence of hyphae which indicated the biological deterioration has happened in some of the boards. Occupational risks were summarised based on the results of the physical and mechanical assessments.